2022
DOI: 10.3389/fcimb.2022.863399
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Profiling of Lung Microbiome in Solid Organ Transplant Recipients Reveals Virus Involved Microecology May Worsen Prognosis

Abstract: Solid organ transplantation (SOT) is the final therapeutic option for recipients with end-stage organ failure, and its long-term success is limited by infections and chronic allograft dysfunction. Viral infection in SOT recipients is considered an important factor affecting prognosis. In this study, we retrospectively analyzed 43 cases of respiratory infections in SOT recipients using metagenomic next-generation sequencing (mNGS) for bronchoalveolar lavage fluid (BALF). At least one virus was detected in 26 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Unfortunately, no herpesvirus is included as a biomarker ( Zhao et al., 2023 ). Our results align with another study that found an association between herpesvirus reactivation and lung microbiota ( Pan et al., 2022 ). On the other hand, the presence of herpesviruses may alter the respiratory environment, leading to changes in the structure of the microbiome.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Unfortunately, no herpesvirus is included as a biomarker ( Zhao et al., 2023 ). Our results align with another study that found an association between herpesvirus reactivation and lung microbiota ( Pan et al., 2022 ). On the other hand, the presence of herpesviruses may alter the respiratory environment, leading to changes in the structure of the microbiome.…”
Section: Discussionsupporting
confidence: 93%
“…investigated the relationship between viruses and prognosis in lung infections in patients undergoing solid organ transplantation. The results showed that CMV was associated with poor prognosis, while TTV was not ( Pan et al., 2022 ).…”
Section: Discussionmentioning
confidence: 98%
“…The diagnosis of pulmonary mixed infections remains challenging but is crucial because clinical manifestations are severe and associate with poor prognosis [ 14 ]. Pulmonary infections associating P. jirovecii and more than one viruses has already been described [ 13 , 19 , 27 , 29 ]. Maartens et al conducted a prospective study including 284 HIV-infected patients with pulmonary symptoms [ 30 ].…”
Section: Disscussionmentioning
confidence: 99%
“…The usefulness of syndromic approach has already been assessed with a multiplex PCR TaqMan ® array card (ThermoFisher) which simultaneously detects 24 viruses (including CMV and HSV 1 + 2), eight bacteria and two fungi (including P. jirovecii ) [ 31 ] and with the “FTD respiratory pathogens 33” kit (Fast-Track Diagnostics, Esch-sur-Alzet, Luxembourg) targeting 33 microorganisms (including P. jirovecii and CMV) [ 30 ]. Recent studies proposed next-generation sequencing methods for a large-scale approach [ 13 , 27 , 29 , 32 ]. These techniques allow thus prompt management of polymicrobial infections frequently associated with a poor prognosis.…”
Section: Disscussionmentioning
confidence: 99%
“…In many cases, the presence of a DNA virus, such as the Torque teno virus (TTV), is considered to be related to the low immunity of patients (Maggi et al, 2011;Görzer et al, 2014). A previous study showed that solid organ transplant recipients with viral and bacterial co-infections had poor prognoses (Pan et al, 2022). mNGS can also detect viruses that cannot be detected by conventional methods; seven types of respiratory DNA viruses were identified by mNGS, with the most commonly detected virus being the human herpesvirus.…”
Section: A B Figurementioning
confidence: 99%